Pemanfaatan Tumpi Jagung Fermentasi pada Penggemukan Domba Jantan Ekor Gemuk - Suci Wulandari; Hariadi Subagja; Siti Mutmainnah (Jurnal Ilmiah Inovasi, 2017)
This study aims to examine the use of fermented corn tumpi on the fat tail sheep fattening and sheep production performance which includes the consumption of feed dry matter (DM), daily weight gain, and feed conversion. The study consisted of three treatments, namely, control diet without tumpi corn fermentation (P0), feed containing 30% tumpi fermentation (P1), and feed containing 60% tumpi corn fermentation(P2). Replicates at each treatment consists of three sheep. The method used in this study is completely randomized design (CRD) using analysis of variance (ANOVA) and significantly different results in a further test using the least significant difference test (LSD). The results showed that the use of fermented corn tumpi are not significantly different (P> 0.05) on dry matter intake. But the use of fermented corn tumpi significantly different (P <0.05) on daily weight gain and feed conversion. Average daily weight gain wasÂ  the highest in P1 of 140.47 grams / head / day.Â Keyword : Sheep, fattening, tumpi corn fermentation